Action mechanism of liquid bridge between electroplated diamond wires for ultrathin wafer slicing. (1st January 2022) - Zheng, Jintao; Ge, Peiqi; Bi, Wenbo; Zhao, Yukang; Wang, Chao
Highlights: A liquid bridge is formed between diamond wires by capillary action, affecting ultrathin wafering. An analysis model for the liquid bridge adhesion between diamond wires is presented. The thinner wafer slicing with the finer wires is more susceptible to liquid bridge. Enhancing wire strength or reducing wire span is conducive to further declining kerf loss and slicing thickness. The formation and effect of liquid bridge are observed by a self-developed experimental device. Abstract: Ultrathin wafer slicing with low kerf loss for electroplated diamond wire sawing is the primary means to improve the productivity in wafering and reduce the manufacturing costs in the photovoltaic industry. Nevertheless, the reduction of the diameter and spacing of the diamond wires makes the liquid bridge action between them significant, which will affect the slicing process. Therefore, based on the principle of minimum potential energy, an analytic model of adhesion caused by the liquid bridge between the diamond wires with protruding abrasives is established in this paper. The variation of the adhesion length with initial wire web gap, wire span, and wire tension as well as wire diameter is analyzed. The results show that the adhesion length was increased with the increase of the wire diameter. The reduction of the initial wire web gap would increase the adhesion length, that was, the limitation of the liquid bridge on the thinner wafers sawing was more obvious. The adhesion length was decreased with the decrease of the wire span or the increase of the wire tension. So it is effective to weaken the limitation of the liquid bridge on the wafers slicing by reducing the wire span or enhancing the wire strength. Then, an experiment on the action of the liquid bridge between the diamond wires was carried out. The theoretical results were in accord with the experimental ones well, and the maximum error was 8.27%. The research work is of great significance to further reduce kerf loss and wafer slicing thickness.